The importance of measuring the uncertainty of HbA1c analysis - Ayyildiz, Hakan; Kalayci, Mehmet (Annals of Medical Research, 2021)
Aim: HbA1c, which reflects blood glucose levels in the last two to three months, has a significant role in the diagnosis, treatment and follow-up of diabetic patients. Measurement uncertainty is defined as the range of possible values, which comprises the measured level. This study aims at showing how to calculate the measurement uncertainty of HbA1c and informing clinicians on its significance for the efficient diagnosis, treatment and follow-up.Materials and Methods: The measurement uncertainty calculating model was used to determine the measurement uncertainty of HbA1c. This model comprises six steps and is constructed depending on European Accreditation Guidelines, described in Nordest Guidelines, Eurolab Technic Report, and ISO/DTS 21748 Guidebook. The HbA1c analysis was chromatographically studied with Trinity Biotech Premier Hb9210 analyzer. Besides internal and external quality control data of HbA1c tests done in Elazig City Hospital in the months between January 2019 and September 2019, data analyses were done to calculate the measurement uncertainty by using the HbA1c test results.Results: The measurement uncertainty of HbA1c was calculated as HbA1c±4.27% using a confidence interval of 95%. These results, were found to be lower than the total allowable error, determined by international organizations. Based on our results, the cut-off value of HbA1c of 6.5% had a measurement uncertainty between 6.2% and 6.8%.Conclusion: We consider that this study will guide the laboratory specialists, concerned with the suggestion that “medical laboratories are required to calculate the measurement uncertainty for quantitative results.” Furthermore, reporting the measurement uncertainty with test results will supply clinicians with information about measurement quality and contribute to creating awareness on this issue.
Keywords: HbA1c; laboratory; measurement uncertainty